DIAGNOSIS GASTROENTERITIS BERBASIS SISTEM PAKAR MENGGUNAKAN METODE FUZZY DAN CERTAINTY FACTOR - Sabilatul Hidayah; Yoannes Romando Sipayung (Universitas Nusa Cendana, 2023)
Gastroenteritis is inflammation of the stomach and intestines with symptoms of diarrhea and often fever. The disease in question is repeated defecation, more than four times, and the type of liquid stool, which can be accompanied by blood or mucus. Digestive disorders this disease occurs due to viruses, bacteria, or parasites. This disease is often underestimated because the symptoms are almost the same as diarrhea, so if it is not handled properly, it can endanger the patient's life, especially with conditions that are getting weaker and worse. This study aims to create an expert system application program that can diagnose Gastroenteritis, the results of which can show the disease suffered by the patient. 16 symptom data will be used, namely Fever above 38C, Chills, Headache, Nausea, Lack of appetite, Easy Drowsiness, Constant thirst, Watery stools, Discomfort, Stomach cramps/bloating, Dehydration, Weight loss, Diarrhea with blood, restlessness, weakness, no urine in the diaper for 3 hours or more. To demonstrate its confidence percentage, the authors chose the Fuzzy Logic and Certainty Factor methods as the basis for calculating the archival samples from the clinic with 100% confidence percentage. Based on the expert system trials and the resulting Certainty Factor values, it can be concluded that the expert system that has been created makes it easier to determine Gastroenteritis so that it can be handled properly and correctly.